Notes to the financial statements: Current state and improvement - Ana Rep (Business Systems Research (BSR), 2021)
Background: Prior studies have revealed a disclosure problem in financial statements, primarily in narrative reports. Three main problem areas have been identified: insufficient relevant information, too much irrelevant information, and low-level communication. Micro and small entities face the most difficulties. Objectives: The main objective of this research is to propose a solution to existing disclosure problems to contribute towards improving the quality of financial reporting of smaller entities. Methods/Approach: To improve the reporting model for smaller entities, a survey has been conducted using a structured questionnaire on a sample of non-financial entities registered in Croatia. Based on results interpretations, standardized notes have been proposed. Results: 167 respondents have shared their thoughts about current disclosure issues and possible improvements, showing their awareness of disclosure problems and willingness for change. Given their opinions, the proposal has been made. Conclusions: The main contribution of the paper is the creation of a proposal for standardized, integrated, and digitalized notes to the financial statements based on the principle of materiality, primarily addressed to micro but also small entities from the non-financial sector. The paper extends previous proposals which did not focus on their structure and digitalization.
Keywords: D22; M19; M41; 330; disclosure problems; financial statements; notes; micro and small entities; standardization; integration; digitalization; the principle of materiality